Efficacy and Safety of Pharmacological and Physical Therapies for Bell's Palsy: A Bayesian Network Meta-Analysis - Shi, Jianwei; Lu, Dafeng; Chen, Hairong; Shu, Mingzhu; Xu, Yang; Qian, Jiaojiao; Ouyang, Ke; Huang, Huaying; Luo, Zhengxiang; Wang, Chunhui; Zhang, Yansong (Frontiers in Neurology, 2022)
Objective: The objective was to comprehensively assess the efficacy and safety of all pharmacological and physical treatments (short-term, ≤ 1 month) for patients with acute Bell’s palsy. Methods: The electronic databases PubMed, Web of Science, Embase, Cochrane Library, and CNKI were searched for randomized controlled trials comparing two or more regimens in patients with Bell’s palsy to be included in a Bayesian network meta-analysis. Odds ratios and confidence intervals for the primary outcome of House-Brackmann scale and secondary outcomes of sequelae (synkinesis and crocodile tears) and adverse events were obtained and subgroup analyses of steroids and antivirals were conducted. Results: Twenty-six studies representing 3609 patients having undergone 15 treatments matched our eligibility criteria. For facial recovery, acupuncture plus electrical stimulation, steroid plus antiviral plus Kabat treatment, and steroid plus antiviral plus electrical stimulation were the top three options based on analysis of the treatment ranking (probability = 84%, 80% and 77%, respectively). Steroid plus antiviral plus electrical stimulation had the lowest rate of sequelae but were more likely to lead to mild adverse events. Subgroup analysis revealed that methylprednisolone and acyclovir were likely to be the preferred option. Conclusions: This network meta-analysis indicated that combined therapies, especially steroid plus antiviral plus Kabat treatment, were associated with a better facial function recovery outcome than single therapy. Other physical therapies, such as acupuncture plus electrical stimulation, may be a good alternative for people with systemic disease or allergies. More high-quality trials of physical regimens are needed in the future.